Laparoscopic pectopexy and paravaginal repair after failed recurrent pelvic organ prolapse surgery - Mehmet Sait Bakir; Ihsan Bagli; Yunus Cavus; Ali Emre Tahaoglu (Wolters Kluwer Medknow Publications, 2020)
Laparoscopic pectopexy has been described recently for pelvic organ prolapse (POP) and it could be an alternative surgery to sacrohysteropexy. A 36-year-old parity 3 women was operated cause of POP, and on her history, she had performed one sacrospinous ligament fixation with colporrhaphy anterior and one abdominal sacrohysteropexy because of POP. After 6-month follow-up, anatomic and functional cures were provided. Laparoscopic pectopexy could be an alternative procedure for recurrent POP surgery with promising results.